2013
DOI: 10.1175/jcli-d-11-00023.1
|View full text |Cite
|
Sign up to set email alerts
|

The Leading, Interdecadal Eigenmode of the Atlantic Meridional Overturning Circulation in a Realistic Ocean Model

Abstract: Variations in the strength of the Atlantic meridional overturning circulation (AMOC) are a major potential source of decadal and longer climate variability in the Atlantic. This study analyzes continuous integrations of tangent linear and adjoint versions of an ocean general circulation model [Océan Parallélisé (OPA)] and rigorously shows the existence of a weakly damped oscillatory eigenmode of the AMOC centered in the North Atlantic Ocean and controlled solely by linearized ocean dynamics. In this particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
83
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 50 publications
17
83
0
Order By: Relevance
“…However, using observational data, Frankcombe et al (2008) observed the signature of large-scale SST and Sea Surface Height anomalies, propagating westward across the North Atlantic ocean. In addition, Sévellec and Fedorov (2013) show that, in a 2° global configuration of the OPA (Océan PArallélisé) model with realistic topography, the least damped mode of variability of the tangent adjoint linear model remains a potential candidate to explain the MOC multidecadal variability (Ortega et al 2015). This mode is characterized by large-scale temperature anomalies that propagate westward across the subpolar gyre, associated with long baroclinic Rossby waves .…”
Section: Summary and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, using observational data, Frankcombe et al (2008) observed the signature of large-scale SST and Sea Surface Height anomalies, propagating westward across the North Atlantic ocean. In addition, Sévellec and Fedorov (2013) show that, in a 2° global configuration of the OPA (Océan PArallélisé) model with realistic topography, the least damped mode of variability of the tangent adjoint linear model remains a potential candidate to explain the MOC multidecadal variability (Ortega et al 2015). This mode is characterized by large-scale temperature anomalies that propagate westward across the subpolar gyre, associated with long baroclinic Rossby waves .…”
Section: Summary and Discussionmentioning
confidence: 95%
“…This mechanism has been shown to be robust to the coupling to a variety of idealized atmospheric models, like energy balance models (Fanning and Weaver 1998;Huck et al 2001) or zonally-averaged statistical-dynamical atmosphere (Arzel et al 2007). This variability was also identified in realistic geometry ocean models, forced by fixed surface fluxes (Sévellec and Fedorov 2013), or coupled to an atmospheric energy balance model (Arzel et al 2012), but with a damped character due to a variety of processes. Introducing a 3D dynamical atmosphere, Buckley et al (2012) recently explored the multidecadal variability arising in two coupled model configurations with simplified flat bottom and bowl oceanic geometry.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…While most observational and modeling studies suggest that the bidecadal oscillations can be largely explained by internal ocean dynamics related to the AMOC and AMO (Huck and Vallis 2001;Von der Heydt and Dijkstra 2007;Danabasoglu 2008;Frankcombe and Dijkstra 2009;Frankcombe et al 2010), others argue that they involve westward-propagating baroclinic Rossby waves of large-scale temperature and sea level anomalies (e.g., Sevellec and Fedorov 2013;Vianna and Menezes 2013). Sevellec and Fedorov (2013) demonstrated that the zonal structures of temperature anomalies alternate between a dipole (corresponding to AMOC variability) and one sign pattern (no AMOC variability). Consistent with this result, Vianna and Menezes (2013) showed that the leading CEOF mode of the bidecadal sea level signals is associated with the AMOC variability, whereas the second CEOF mode has distinguishable westward-propagating thermal Rossby waves and is not apparently related to AMOC change.…”
Section: Atlantic Multidecadal Oscillation (Amo)-related Sea Level Pamentioning
confidence: 99%
“…This re-normalization factor is thus a way to go from a global initial uncertainty to the local one. This last expression allows us to write the predictive power as: where 2 ∞ = 2 (∞) = 2 sto (∞), since lim t→∞ 2 ini (t) = 0 (i.e., the system is asymptotically stable, Sévellec and Fedorov 2013). This leads to the property that This gives a lower and upper theoretical bounds to the predictive power.…”
Section: Methodsmentioning
confidence: 99%